Asteroid 2008 TC3, not a polymict ureilitic but a polymict C1 chondrite parent body? Survey of 249 Almahata Sitta fragments. (14th May 2022) - Bischoff, Addi; Bannemann, Lukas; Decker, Stephan; Ebert, Samuel; Haberer, Siegfried; Heitmann, Ursula; Horstmann, Marian; Klemm, Kerstin I.; Kraemer, Ann‐Kathrin; Lentfort, Sarah; Patzek, Markus; Storz, Jakob; et al.
Abstract: On October 7, 2008, the asteroid 2008 TC3 exploded as it entered the Earth's atmosphere, producing significant dust (in the atmosphere) and delivering thousands of stones in a strewn field in Sudan, collectively known as the Almahata Sitta (AhS) stones. About 600 fragments were officially recovered in 2008 and 2009. Further rocks were collected since the fall event by local people. From these stones, 249 were classified at the Institut für Planetologie in Münster (MS) known as MS‐xxx or MS‐MU‐xxx AhS subsamples. Most of these rocks are ureilitic in origin (168; 67%): 87 coarse‐grained ureilites, 60 fine‐grained ureilites, 15 ureilites with variable texture/mineralogy, four trachyandesites, and two polymict breccias. We identified 81 non‐ureilitic fragments, corresponding to 33% of the recovered samples studied in Münster. These included chondrites, namely 65 enstatite chondrites (43 EL; 22 EH), 11 ordinary chondrites (OC), one carbonaceous chondrite, and one unique R‐like chondrite. Furthermore, three samples represent a unique type of enstatite achondrite. Since all AhS stones must be regarded as individual specimens independent from each other, the number of fresh ureilite and enstatite chondrite falls in our meteorite collections has been increased by several hundred percent. Overall, the samples weigh between <1 and 250 g and have a mean mass of 15 g. If we consider—almost 15 years after the fall—the mass calculations, observations during and after the asteroid entered the atmosphere, the mineralogy of the C1 stones AhS 91A and AhS 671, and the experimental work on fitting the asteroid spectrum (e.g., Goodrich et al., 2019; Jenniskens et al., 2010; Shaddad et al., 2010), the main portion of the meteoroid was likely made of the fine‐grained (carbonaceous) dust and was mostly lost in the atmosphere. In particular, the fact that C1 materials were found has important implications for interpreting asteroid 2008 TC3 's early spectroscopic results. Goodrich et al. (2019) correctly suggested that if scientists had not recovered the "water‐free" samples (e.g., ureilites, enstatites, and OC) from the AhS strewn field, 2008 TC3 would have been assumed to be a carbonaceous chondrite meteoroid. Considering that the dominating mass of the exploding meteoroid consisted of carbonaceous materials, asteroid 2008 TC3 cannot be classified as a polymict ureilite; consequently, we state that the asteroid was a polymict carbonaceous chondrite breccia, specifically a polymict C1 object that may have formed by late accretion at least 50–100 Ma after calcium–aluminum‐rich inclusions.